Some theoretical models for solitary structures of boundary layer waves - Lakhina, G. S.; Tsurutani, B. T.; Singh, S. V.; Reddy, R. V. (My University, 2003)
Solitary electrostatic structures have been observed in and around auroral zone field lines at various altitudes ranging from close to the ionosphere, to the magnetopause low-latitude boundary layer (LLBL) and cusp on the dayside, and to the plasma sheet boundary layer on the night-side. In this review, various models based on solitons/double layers and BGK modes or phase space holes are discussed in order to explain the characteristics of these solitary structures.
Keywords: Theoretical models; Boundary layer waves; Low-latitude boundary layer (LLBL); Nonlinear ion cyclotron waves; Cyclotron waves